The Impact of Changing Social Support on Older Persons' Onset of Loneliness During the COVID-19 Pandemic in the United Kingdom. (2nd March 2022) - Vlachantoni, Athina; Evandrou, Maria; Falkingham, Jane; Qin, Min
Abstract: Background and Objectives: Social distancing measures aimed at controlling the spread of coronavirus disease 2019 (COVID-19) are likely to have increased social isolation among those older than 70 instructed to shield at home. This study examines the incidence of loneliness by gender over the first 10 months of the COVID-19 pandemic among persons aged 70 and older in the United Kingdom, and the impact of changing social networks and perceived social support on the new occurrence of loneliness. Research Design and Methods: Participants ( N = 1, 235) aged 70 and older with no reports of loneliness before the pandemic who participated in 7 rounds of the Understanding Society: COVID-19 Study (April 2020–January 2021) and the main Understanding Society Study conducted during 2019. Cox regression analyzed the time to a new occurrence of loneliness. Results: Among older people who hardly ever/never felt lonely before the pandemic, 33.7% reported some degree of loneliness between April 2020 and January 2021. Living in a single-person household, having received more social support before the pandemic, changes in support receipt during the pandemic, and a deteriorating relationship with one's partner during the pandemic increased the risk of experiencing loneliness. Older women were more likely than older men to report loneliness, even when living with a partner. Discussion and Implications: During the 3 COVID-19-related lockdowns in the United Kingdom, changes in older people's social networks and support resulted in a significant onset of loneliness. Findings highlight the risks of shielding older persons from COVID-19 in terms of their mental well-being and the importance of strengthening intergenerational support.